2011
DOI: 10.1088/0953-8984/23/35/355901
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependences of piezoelectric, elastic and dielectric constants of L-alanine crystal

Abstract: Temperature changes in the components of piezoelectric, elastic and dielectric tensors were studied in L-alanine crystals in the range 100-300 K. A jumpwise increase in the c(55) component of the elastic stiffness accompanied by maxima in damping of all face-shear modes observed at 199 K in L-alanine crystal were interpreted as a result of changes in the NH(3)(+) vibrations occurring through electron-phonon coupling. All components of the piezoelectric tensor show small anomalies in this temperature range. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…We can compare the computed maximum strain constants in Table I of up to 18 pm=V to our recently calculated, much smaller piezoelectric constants for L-alanine single crystals, in the range of 4-6 pC=N [26] (experimental values are similar, ranging from 2 to 4 pC=N) [40]. The elastic stiffness constants of DL alanine range from 7 to 67 GPa (Supplemental Material Table S1 [41]) and are almost identical to those of L alanine.…”
mentioning
confidence: 56%
“…We can compare the computed maximum strain constants in Table I of up to 18 pm=V to our recently calculated, much smaller piezoelectric constants for L-alanine single crystals, in the range of 4-6 pC=N [26] (experimental values are similar, ranging from 2 to 4 pC=N) [40]. The elastic stiffness constants of DL alanine range from 7 to 67 GPa (Supplemental Material Table S1 [41]) and are almost identical to those of L alanine.…”
mentioning
confidence: 56%
“…Most amino acids exist in a chiral symmetric group, l or d form, and thus exhibit a piezoelectric response. Generally these chiral symmetric group crystals allow shear piezoelectric tensors, d 14 , d 25 , and d 36 , but no longitudinal piezoelectric tensors such as d 11 , d 22 , and d 33 55–61. However, the longitudinal piezoelectric tensor in piezoelectric materials is significantly important, and has great advantages for practical piezoelectric applications, because most of the environmentally available types of mechanical forces are of compressive or tensile direction.…”
Section: Piezoelectricity Of Amino Acidsmentioning
confidence: 99%
“…Generally these chiral symmetric group crystals allow shear piezoelectric tensors, d 14 , d 25 , and d 36 , but no longitudinal piezoelectric tensors such as d 11 , d 22 , and d 33 . [55][56][57][58][59][60][61] However, the longitudinal piezoelectric tensor in piezoelectric materials is significantly important, and has great advantages for practical piezoelectric applications, because most of the environmentally available types of mechanical forces are of compressive or tensile direction. Very recently, theoretical and experimental studies of the longitudinal piezoelectricity of chiral amino acid crystal films have been reported.…”
Section: Piezoelectricity Of Amino Acidsmentioning
confidence: 99%
“…Moreover, the impact of amino acid in the field of physical research is clearly shown. One example is the piezoelectric property of L-alanine (Tylczyński et al 2011), which is represented in Fig. 2.43.…”
Section: Discussionmentioning
confidence: 99%
“…Lechuga-Ballesteros and Rodriguez-Hornedo (1993) reported data on crystal growth, morphology, and the influence of additives. Moreover, the crystal physics of L-alanine were investigated in detail (Tylczyński et al 2011): The piezoelectric, elastic, and dielectric tensors of L-alanine were measured in the temperature range of 100 to 300 K. L-Alanine was found to be weakly piezoelectric; moreover, a jumpwise increase in the c 55 component of the tensor of elastic stiffness was observed, which was attributed to a change of the vibrations of the amino group.…”
Section: Alaninementioning
confidence: 99%